ATIM-36. TEM-GBM-001 STUDY: AUTOLOGOUS CD34+ ENRICHED HEMATOPOIETIC PROGENITOR CELLS GENETICALLY MODIFIED FOR HUMAN INTERFERON-α2 & ADMINISTERED TO PATIENTS WITH GLIOBLASTOMA & AN UNMETHYLATED MGMT PROMOTER. (11th November 2019) - Finocchiaro, Gaetano; Gentner, Bernhard; Ciceri, Fabio; DiMeco, Francesco; Legnani, Federico; Eoli, Marica; Pollo, Bianca; Farina, Francesca; Zambanini, Andrew; Mazzoleni, Stefania; Russo, Carlo; Naldini, Luigi
Abstract: BACKGROUND: Most patients with GBM & an unmethylated O-6-methylguanine-DNA methylase (MGMT) gene promoter, have a poor prognosis with approximately 20% of patients surviving to 2 years. Poor prognosis is likely related to factors including a highly immunosuppressive tumor microenvironment (TME). The TME in GBM is mainly composed of tumor associated macrophages (TAMs) & microglia. A subset of tumor-infiltrating macrophages characterized by expression of the angiopoietin receptor Tie2 (TEMs) have features of M2-TAMs, promote tumor angiogenesis & are infrequently found in normal organs. Tie2 is significantly upregulated upon homing to tumors. Gene therapy technology has allowed TEMs to be used as carriers for the local and tumor restricted release of interferon-α (IFN). IFN has antitumor effects, inhibits angiogenesis & modulates the immune system. Cell-based delivery of IFN into the TME by TEMs is expected to provide efficacy, taking advantage of pleiotropic anti-tumor effects & avoiding tolerability issues associated with systemic IFN treatment. We are currently conducting a Phase I/IIa clinical study in Milan (INCB & OSR) to evaluate this therapeutic approach (Temferon) in 21 patients with GBM & unmethylated MGMT promoter (EudraCT Number 2018-001404-11). Eligible patients are identified immediately after first surgical resection. After screening, harvesting of HSPCs occurs followed by 6 weeks of radiotherapy. Non-myeloablative conditioning consists of BCNU & thiotepa followed by administration of non-manipulated HSPCs and Temferon. RESULTS: In Part A of the study, 3 cohorts of 3 patients will receive escalating doses of Temferon. After Part A, a single dose of Temferon will be studied in a further 12 patients (Part B). Criteria for study eligibility are the same for both Part A and Part B. Part A is ongoing with the first 2 patients recruited (June 2019) and Temferon is scheduled for administration. An update on the status and progress of the study will be provided.